Animal Models for the Study of Pulmonary Hypertension: Potential and Limitations - Nogueira-Ferreira, Rita; Faria-Costa, Gabriel; Ferreira, Rita; Henriques-Coelho, Tiago (Cardiology and Cardiovascular Medicine, 2016)
Pulmonary hypertension (PH) is a multifactorial disease, commonly associated with heart failure. Different experimental models have emerged to help in the understanding of the molecular and cellular mechanisms associated with human PH, providing also a useful approach to test experimental therapies for PH treatment. Although there is no ideal animal model that mimics human PH, animal models have clearly provided valuable insights into the characterization of the cellular and molecular pathways underlying PH onset and progression, and have been successfully applied in the discovery of novel therapeutic approaches. In here we summarize the features of the animal models described within the field of PH research, either the physical, chemical and genetic models, emphasizing its advantages and limitations.